Réponses

  • Utilisateur Brainly
2014-03-26T11:20:10+01:00
C'est (x+3)(3x-4)+(6x-2)(4x+2) = utiliser la double distributivité

(x*3x + x*-4 + 3*3x + 3*-4)+(6x*4x + 6x*2 -2*4x -2*2) =

3x²-4x+9x-12+24x²+12x-8x+4 = tu réduis
Attention, le dernier terme de la forme développée est -4 :)
2014-03-26T11:20:45+01:00
Bonjour,

(x+3)(3x-4)+(6x-2)(4x+2) = (3x² - 4x + 9x - 12) + (24x² + 12x - 8x - 4)
                                    = 3x² - 4x + 9x - 12 + 24x² + 12x - 8x - 4
                                    = 27x² + 9x - 16